Notes on Field Survey and Distributional Record of Small Mammals in Mount Murud, Sarawak, Malaysia - Wiantoro, Sigit; Lit, Eileen; Sidq, Mohd Fizl; Nor Salmizar, -; Sait, I.; Abdullah, M.T (Journal of Tropical Biology and Conservation, 2009)
Mount Murud is the highestmountain in Sarawak. It has high diversity andendemism of flora and fauna. Small mammalsurvey in Mount Murud was conducted inOctober 2008 using mist nets and live traps. Atotal of 17 individuals of small mammalcomprising five species of Chiroptera, onespecies of Insectivora and one species of Scandentia were recorded. Pipistrellus javanicus (Chiroptera: Vespertilionidae) and Hylomys suillus (Insectivora: Erinaceidae) arenew records for Mount Murud.